Finite Element Analysis of a Novel Fusion Strategy in Minimally Invasive Transforaminal Lumbar Interbody Fusion. (11th May 2022) - Han, Zhenchuan; Ren, Bowen; Zhang, Long; Ma, Chao; Liu, Jianheng; Li, Jiantao; Liu, Xiao; Liu, Qingzu; Mao, Keya; Tang, Peifu
Abstract : Purpose. To evaluate the biomechanics of a novel fusion strategy (hybrid internal fixation+horizontal cage position) in minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF). Methods. MIS-TLIF finite element models for three fusion strategies were created based on computed tomography images, namely, Model-A, hybrid internal fixation (ipsilateral pedicle screw and contralateral translaminar facet screw fixation)+horizontal cage position; Model-B, bilateral pedicle screw (BPS) fixation+horizontal cage position; and Model-C, BPS fixation+oblique 45° cage position. A preload of 500 N and a moment of 10 Nm were applied to the models to simulate lumbar motion, and the models' range of motion (ROM), peak stress of the internal fixation system, and cage were assessed. Results. The ROM for Models A, B, and C were not different (P > 0.05 ) but were significantly lower than the ROM of Model-INT (P < 0.0001 ). Although there were subtle differences in the ROM ratio for Models A, B, and C, the trend was similar. The peak stress of the internal fixation system was significantly higher in Model-A than that of Models B and C, but only the difference between Models A and B was significant (P < 0.05 ). The peak stress of the cage in Model-A was significantly lower than that of Models B and C (P < 0.01 ). Conclusion. Hybrid internal fixation with horizontal single cage implantation can provide the same biomechanical stability as traditional fixation while reducing peak stress on the cage and vertebral endplate.